Visualizing Sovereignty in the Time of Biometric Sensors - Rickard, Jolene (South Atlantic Quarterly, 2011)
Multiple expressions of sovereignty beyond a narrow legal interpretation are discussed through the artwork of contemporary Iroquois artists, G. Peter Jemison (Seneca), Alan Michelson (Mohawk), Samuel Thomas (Cayuga), and Marie Watt (Seneca). Michelson's installation at the Massena homeland security border checkpoint between the United States, Canada, and the Mohawk Nation, titled The Third Bank of the River, draws on the Guswentah or Two Row Wampum underscoring the problematic yet ongoing assertion of Haudenosaunee sovereignty. A link is made between the work of these artists and the 2008 Courtney Hunt film, Frozen River, based on the cultural and political understanding of the Two Row Wampum. The Guswentah is discussed as a demonstration of sovereignty and is historicized through Cayuga chief Deskaheh's call for the recognition of Haudenosaunee sovereignty at the League of Nations in Geneva, in 1923, John Mohawk's 1978 Basic Call to Consciousness, and more recently, Taiaiake Alfred's 1999 Peace, Power, Righteousness. These artists demonstrate the critical role they play in the ongoing formation of sovereignty as a visual or aesthetic issue in conjunction with its historic legal positioning.
Keywords: 1-Histoire de l'art; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé